In silico prediction and in vivo validation of Daphnia pulex microRNAs. - Shuai Chen (Public Library of Science (PLoS), 2014)
Daphnia pulex, the crustacean with the first sequenced genome, is an important organism that has been widely used in ecological and toxicological research. MicroRNAs (miRNAs) are 21-25 nucleotide small non-coding RNAs that are involved in a myriad of physiological processes. In this research, we predicted 75 D. pulex miRNAs by sequence homology and secondary structure identification from the full genome sequence. Fourteen predicted miRNAs were selected for quantitative real time polymerase chain reaction (RT-PCR) validation. Out of these, eight (mir-8, mir-9, mir-12, mir-92, mir-100, mir-133, mir-153 and mir-283) were successfully amplified and validated. Next, expression levels were quantified at three different life stages (days 4, 8 and 12 of age) using U6 spliceosomal RNA as a reference gene. The expression of mir-8, mir-9, mir-12, mir-92 and mir-100 significantly differed across time suggesting these microRNAs might play a critical role during D. pulex development. This is the first study to identify and validate miRNAs in D. pulex, which is an important first step in further studies that evaluate their roles in development and response to environmental and ecological stimuli.